Hardiness Behavior of Reporters in Covering News - Dwi Hurriyati (Cita Konsultindo Research Center, 2023)
Journalists in finding news must keep pace with the times and reporters from other media. Delay in working on the news (deadline), not announced. News that is not interesting, must be published. Seeing this hard work, it is necessary to support faith and violence at every step and this is not needed by everyone. The purpose of this study was to determine the relationship between hardiness and self-efficacy in the general daily in the city of Palembang. The survivors variable in this study is self-efficacy, while hardiness is the independent variable. This study uses a scale of self efficacy and hardiness. This research uses quantitative methods. The sample used in this study amounted to 245 people in Palembang. This study shows that there is a very significant relationship between the hardiness variable and the self efficacy variable in the general daily report in Palembang with a value of F = 20,028, Adjusted R Square = 0,216, p = 0,000 because of the significance of (p) 0,000 significance value of p <0, 01 So stated there is a very significant relationship